(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2023)
The objective of this study was to evaluate the possibility of promoting rooftop rainwater harvesting to address future water scarcity in the Oxford College of Engineering and Management Nawalparasi district. AutoCAD software drew accepted plans and maps; manual measurement was done with measuring tape since some parts were missing. The results show that the linear forecast 1558.139, 1581.57mm,1548.63mm, 1598.14mm and 1570.64mm. The volume of water is 5135.54, 5028.16, 5188.94, 5099.68 respectively. It also shows the calculation of water demand which is 5,820,000 liters per year, and the water harvested is 5188946.58 liters per year. Finally, with this ratio, we realized we could fulfil 89.15% of water demand through water harvesting. The time series relevant results indicated that the A.R.I.M.A. model of forecasting rainfall was based on (0.1.0), signifying the R Square value is .631 and the p-value is insignificant (p > 250), which is better for this forecasting model.